Spanning capacity analysis of self-anchored suspension bridges based on the stability and compression strength of stiffening girder - Cunyu Cui; Changyan Niu; Jianguo Dai; Yongcheng Lu (Journal of Asian Architecture and Building Engineering)
Considerable axial compression stress exists in the stiffening girder of self-anchored suspension bridges. Therefore, failures of self-anchored suspension bridges will be either due to material failure or instability of the stiffening girder, which will be the major concerns. In this study, the spanning capacity of self-anchored suspension bridges is studied based both on the stability and compression strength of the stiffening girder. Theoretical analysis reveals that, due to the elastic supports provided by the main cables and suspenders, in-plane elastic buckling of the stiffening girder is prevented. However, the stiffening girder may still buckle in the transverse direction. The extreme span length of self-anchored suspension bridges increases as the rise-to-span ratio increases. For general bridge designs, when the rise-to-span ratio is smaller than that of a bridge-specific turn point value, the spanning capacity of self-anchored suspension bridges is directly proportional to the rise-to-span ratio; however, when the rise-to-span ratio is larger than that of the turn point value, the spanning capacity of self-anchored suspension bridges is proportional to the 1/3rd power of the rise-to-span ratio. Besides, the spanning capacity of self-anchored suspension bridges will increase as the width or yielding strength of the stiffening girder increases.